A STUDY OF INMATE ARGOT IN ROMANIAN PRISONS - NADRAG, Lavinia; STROESCU, Manuela (Comparative Legilinguistics, 2010)
The lexis and structure of prison argot reflect the personalities of inmates who employ them, as well as the conflicts and tensions inherent in prison settings. It is shown in this article that the distinctiveness of prison argot is largely a product of the character of penal context. Its extent of use varies with the extent of penal discipline. Appreciation of this complex relationship might facilitate improved communication between prisoners and custodial authorities. In addition, knowledge of prison argot meanings has a potential to improve the management of prison-based programs and thus appears helpful in the complex process of prisoners' rehabilitation and social reintegration.